Introduction: Taking stock of security and finance - Nina Boy; John Morris; Mariana Santos (Finance and Society, 2017)
When, seven years ago, Marieke de Goede first drew attention to the historical and conceptual entanglements between the logics of finance and security, and to the artificial - yet meaningful - divide between the two in modernity, this was not merely a call for a new research programme. Attempting to hold together these two objects of disciplinary enquiry, and becoming aware of the tendency to collapse one into the other inherent to International Political Economy (IPE) or International Relations (IR) analytics, was also a much needed exercise of disciplinary critique, consistent with interrogating divides between the economic and the social, the financial and cultural. In other words, more than just a new object or field of empirical and theoretical research, the finance-security nexus was proposed as a device for critically and genealogically thinking through distinct disciplinary approaches to economy, futurity and populations. To that end, this special issue proposes to take stock of the multiple ways in which the finance-security nexus has been deployed as such a device of (post)disciplinary critique.
Keywords: 300